Nutrient removals by 21 aquatic plants for vertical free surface-flow (VFS) constructed wetland - Iamchaturapatr, Janjit; Yi, Su Won; Rhee, Jae Seong (ELSEVIER SCIENCE BV, 2007)
An attempt was made to investigate the removal of high nutrient contents from polluted water. This study focused on the comparisons between nitrogen and phosphorus removal rates by area-based calculation and biomass-based calculation using various kinds of aquatic plants (18 emergent and 3 floating plants). Results showed that all floating plants performed maximum nutrient removal rates based on plant weight calculation while most emergent plants performed maximum nutrient removal rates based on planted area calculation. The reason is that the weights of rooted mass by emergent plants are heavier than their shoots, resulting to low nutrient removal efficiencies in terms of their total weight. The study suggests that the planted area and the plant's geometries (such as roots and shoots) should be considered for the effective design in aquatic plant treatment systems. (C) 2006 Published by Elsevier B.V.
Keywords: WASTE-WATER-TREATMENT; PHOSPHORUS REMOVAL; NITRATE REMOVAL; RHIZOSPHERE; GROUNDWATER; PERFORMANCE; MACROPHYTES; VEGETATION; MICROCOSMS; SYSTEMS